Landscape revisited - Teng Lang Po / Julia Alissa Jamali and Azrul Bahaluddin - Jamali, Julia Alissa; Bahaluddin, Azrul (Faculty of Art and Design, 2021)
The Landscape Revisited brings together the art of paper collage based on local heritage urban context. Through its decrypted visual content, it gives a general overview of the work of art. The viewers interpret the meanings of the work of art based on their cultural background and life experiences. Nevertheless, because the production of this collage art is based on the interpretation of the elements and principles of art and design, this work of art forms a strong connection between theory and perception to the visual scope portrayed. Indirectly this collage art does not limit the thought of interpreting the content without compromising the heart of it, which refers to the character of a heritage urban context. The process of producing this work of art begins with understanding the content of the visual scope that has been selected. In this work, the visual significance is the heritage and historical value of the Kuala Terengganu Chinatown. Known as Teng Lang Po and located at the mouth of the Terengganu River, Kuala Terengganu’s Chinatown has existed for more than 300 years as a formal Chinese settlement. The entrance arch, recognisable by its bold motifs and dragons crowning the top, marks the start of the Jalan Kampung Cina, Kuala Terengganu Chinatown. With the mix of colours and warm atmosphere, it always evokes the charm, traditional feel and is extremely rich in heritage and historical values.